1982
DOI: 10.1093/ajcn/36.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Changes in certain blood constituents during Ramadan

Abstract: Fasting serum cholesterol, triglycerides, thyroxine, triiodothyronine, uric acid, gastrin, and insulin were measured in a group of 24 Muslims at the beginning and end of Ramadan--the Muslim month of fasting. There was a significant increase in the levels of total serum cholesterol, thyroxine, and uric acid and a significant fall in body weight. There was no significant change in the levels of total serum triglycerides, triiodothyronine, gastrin, insulin (fasting), or in the rise in gastrin or insulin 1/2 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
86
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 12 publications
9
86
0
1
Order By: Relevance
“…The methodological quality of the included studies was moderate, with a median score (stars) of 7 out of a possible 9 (interquartile range: [6][7][8]. No study was omitted due to poor quality.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodological quality of the included studies was moderate, with a median score (stars) of 7 out of a possible 9 (interquartile range: [6][7][8]. No study was omitted due to poor quality.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…1 Flowchart showing the selection of studies included in the present systematic review of Ramadan fasting effects on body weight (*two studies reported the effects of Ramadan fasting in healthy and obese subjects, and in healthy and diabetic subjects) Table 1 provides detailed information on the studies used in the meta-analysis (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and descriptive statistics of their characteristics. The average number of subjects per study was 35?8 (SD 27?9) and the subjects' average age was 29?4 (SD 6?4) years old.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of Indonesian people are Muslims, who are obliged to fast (total abstinence from food and drink) for as long as 14 h (from 0330 to 1730) each day for a month. Many studies have been conducted to evaluate the impact of Ramadan fasting on various aspects of health, including lipid metabolism (Fedail et al, 1982;El Arnoaty and Johnson, 1991;Adlouni et al, 1997), acute coronary heart disease and respiratory system (Temizhan et al, 1999;Ramadan and Barac-Nieto, 2000), water balance (Duncan et al, 1990;Schmahl and Metzler, 1991;Leiper et al, 2003;Basiri et al, 2004), dietary intake, endocrine function, serum fructosamine, and clinical, anthropometrical, and most biological parameters (Habbal et al, 1998;Perk et al, 2001;Beltaifa et al, 2002;Ramadan, 2002;Gharbi et al, 2003;Gustaviani et al, 2004;Kassab et al, 2004;Yucel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…First, all of these studies focused exclusively on fasters (Fedail et al, 1982;Frost and Pirani, 1987;Hussain et al, 1987;Hallak and Nomani, 1988;Ch'ng et al, 1989;Iraki et al, 1997;Bigard et al, 1998;Perk et al, 2001;Beltaifa et al, 2002;Ramadan, 2002;Roky et al, 2004) and neglected nonfasters, who constitute an important control group. Second, because blood sampling during fasting is often regarded as intrusive, many of these studies were conducted with small sample sizes, and some studies involved gender-mixed sampling (Hussain et al, 1987;Habbal et al, 1998) or sampling after Ramadan rather than during Ramadan (Yucel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%